A Taiwanese population-based study on the association between chronic tonsillitis and tonsil cancer - Hung, Shih-Han (Oncotarget, 2018)
Although it is known that inflammatory processes elevate the risk of cancer, to date the association between chronic tonsillitis and tonsil cancer remains unknown. This study aimed to evaluate the association of chronic tonsillitis with tonsil cancer based on a population-based database in Taiwan. We retrieved data for this study from the Longitudinal Health Insurance Database 2005. This case-control study included 489 patients with tonsil cancer and 2445 matched controls. We used conditional logistic regression analyses to calculate the odds ratio (OR) and corresponding 95% confidence interval (CI) for having been previously diagnosed with chronic tonsillitis between patients with tonsil cancer and the controls. We found that of the 2934 sampled patients, 22 (0.75%) had received a diagnosis of chronic tonsillitis. A Chi-squared test further revealed that there was a significant difference in the prevalences of prior chronic tonsillitis between tonsil cancer patients and controls (2.45% vs. 0.41%, p<0.001). The conditional logistic regression suggested that after adjusting for hypertension, diabetes, hyperlipidemia, obesity, tobacco use disorder, and alcohol abuse/alcohol dependency syndrome, the OR of having previously been diagnosed with chronic tonsillitis for patients with tonsil cancer was 8.07 (95% CI: 3.32∼19.64; p<0.001) compared to controls. It is also noteworthy that alcohol abuse/alcohol dependency syndrome was significantly associated with TC (adjusted OR=9.88). We demonstrated that patients with chronic tonsillitis were more likely to have tonsil cancer, and our findings support tonsillitis as a possible risk factor for tonsil cancer.